1989
DOI: 10.5144/0256-4947.1989.3
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Intracranial Space-Occupying Lesions: The Experience of the King Khalid University Hospital

Abstract: Based on retrospective analysis of 212 cases diagnosed and treated at the King Khalid University Hospital in Riyadh over a period of 5 years, this study is the first attempt to provide preliminary data on intracranial space-occupying lesions in Saudi Arabia. There were 184 (87%) neoplasms and 28 (13%) nonneoplastic tumors, mostly inflammatory masses. Age and sex distribution was comparable with that reported from other studies. Neuroepithelial tumors comprised 39.7% of all intracranial neoplasms, followed by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
2
22
1
Order By: Relevance
“…[1][2][3] These figures are higher than those reported from European and Asian countries, [5][6][7][8][9][10] but comparable to the percentages derived from Africa. [11][12][13] Both age and sex distributions of our patients are within the reported limits.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…[1][2][3] These figures are higher than those reported from European and Asian countries, [5][6][7][8][9][10] but comparable to the percentages derived from Africa. [11][12][13] Both age and sex distributions of our patients are within the reported limits.…”
Section: Discussioncontrasting
confidence: 50%
“…[1][2][3] However, data concerning the age and sex distributions, anatomic locations, mode of presentation, and standards of management of meningioma in Saudi Arabia have been deficient. This has prompted our study of intracranial meningiomas in this country.…”
mentioning
confidence: 99%
“…Most of them were small, and they reported all types of brain tumors including meningioma, pituitary adenomas, brain metastasis…etc. The percentage of neuro-epithelial brain tumors in these studies were quite small to make any statistical comparisons [11][12][13] One study from King Fahad University Hospital (KFUH) -Al-Khobar in the Eastern province of Saudi Arabia had a larger sample with a sizable percentage of neuro-epithelial brain tumors. The study included all CNS tumors according to the WHO classifications (1979 edition).…”
Section: Histology Type Kfsh-d (%)mentioning
confidence: 99%
“…7,9,11,[13][14][15] The reason for the low number of females among our patients is not clear, considering that the overall male-to-female ratio for all pituitary adenomas treated in our unit was within the ranges reported by other authors. 16 It is possible, however, that the high proportion of non-Saudi acromegalic patients in this series have played a role. A recent census in 1992 revealed that 70.4% of all non-Saudis residing in Saudi Arabia were males.…”
Section: Discussionmentioning
confidence: 70%